The Commitment of Senior Civil Servants to Democratic Freedoms and Equality - Miro HACEK (Transylvanian Review of Administrative Sciences, 2012)
In modern democracies, senior civil servants have outgrown their classic role of mere implementers of orders given by politicians. Both senior civil servants and politicians serve the same democratic state, and both are heirs to the democratic evolution. Our hypothesis is based mainly on the historically developed division of labor between bureaucracy and politics. Senior civil servants have never been tasked with creating the conditions for more democracy in the state, but instead with creating the conditions for a more effective and successful state. Given that political bodies in which politicians operate have been established as the institutionalized personification of democracy, the task of politicians is above all the promotion of democracy, its values and norms. We have tested that hypothesis on the case of Slovenian senior civil servants and politicians and found out, that both elites are favorable to political freedoms and political equality.